The Effect of Using E-Payment and Social Media on Purchasing Decisions at Alfamart in Medan City - Valen Marcella Dinata; Desma; Irvan Rolyesh Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
Companies carry out marketing strategies in order to achieve sales targets by means of sales promotions offered and provide ease of transactions in the form of the availability of digital wallet payment tools with the aim that consumers make purchasing decisions on a product. This study aims to analyze the effect of e-payment and social media both partially and simultaneously on purchasing decisions at alfamart in medan city. This research is descriptive research with a quantitative approach. The sample amounted to 110 respondents selected through non-probability sampling with incidental sampling technique. Data collected through questionnaires. The collected data were analyzed by multiple linear regression. The results showed that the significance of the influence of the e-payment variable (X1) and Instagram social media (X2) on the purchasing decision variable (Y) was 45.2% that the independent variables (X1 & X2) could have an influence on the dependent variable (Y) while the remaining 54.8% was influenced by other factors that came from outside this research model such as price, product quality, promotion, location, satisfaction, and various other variables.